Implementasi Toleransi Antar Umat Beragama di Desa Kolam Kanan Kecamatan Barambai Kabupaten Barito Kuala - Siti Patimah (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
Kolam Kanan Village is a village where people have three different religions. Religions that exist in the village namely Hindu, Muslim and Christian. Although they live in an environment with different beliefs, but the implementation of related public high tolerance of theists. Through some manner by the community it will be able to create inter-religious tolerance environment sector in the community.This study aims to determine how the community receives the difference between religious communities, the community recognizes how inter-religious rights and to know how the people appreciate the existence of inter-religious.The study was designed and conducted using qualitative research methods. Data was collected through observation, interview. Analysis of the results of the research is the analysis of the data reduction step, the presentation of the data and drawing conclusions.The results of this study indicate that the way society and accept differences among religious communities in the village of Kolam Kanan is to be consulted in case of disagreement, deepen and carry theology respectively. Then how society recognizes the right of inter-religious is to recognize the right of others to embrace the religion according to their respective beliefs and religions recognize the right to carry out worship in accordance with his beliefs, and recognize the right of participation in the culture of the people in the Kolam Kanan village. Next is how the public in appreciating the existence of the relationship between religious communities and interact in several areas such as economic and social life.Based on these results, it may be advisable to retain attitudes that are able to create tolerance and improve existing intolerance that still exists in some small communities in Kolam Kanan village.Keywords: tolerance, religious